(untitled) (Indian Journal of Public Health Research & Development, 2025)
Alcohol use Disorder( AUD) poses a significant global public health challenge due to its widespread prevelance and substantial impact on individuals and society. Depsite existing pharmacological and psychosocial interventions, treatment outcomes remain varied abd often suboptimal. This review explores the efficacy, safety and mechanistic actions of both established and novel pharmacotherapies of AUD. Methodologically literature from PubMed, Google scholar and Embase was reviewed to identify relevant studies published between 1990 and 2023. Findings indicate varying degree of effectiveness and safety profiles among different pharmacotherapies, underscoring the importance of personalized treatment approaches to individual patient characteristics and comorbidities. The review concludes with implications for clinical practise and future research directions aimed at optimizing treatment for AUD.